Impact of individual factors and personality trait on psychological problems of family members living with staff of a COVID‐19 frontline hospital: A cross‐sectional self‐administered anonymous questionnaire survey - Shinya Uenishi; Momoko Buyo; Seiji Sato; Hiroko Kojitani; Ryo Odachi; Toshiko Matsuoka; Yuka Okuda; Sohei Kimoto; Masaya Hironishi; Shun Takahashi (PCN Reports, 2023)
Abstract Aim This study aims to evaluate the association between individual factors/personality traits and depression and anxiety in family members living with staff working on the frontline of COVID‐19 care. Methods The subjects were family members over the age of 15 years living with staff members of a COVID‐19 frontline hospital. Between March 27 and April 11, 2021, 204 self‐administered anonymous questionnaires were distributed, and 149 responses were received. Symptoms of depression and anxiety were assessed using the Hospital Anxiety and Depression Scale (HADS). Personality trait was assessed using the Big Five personality traits, and fear of COVID‐19 was assessed using the Fear of COVID‐19 Scale. We examined associations between HADS depression or anxiety scores with individual background factors, scores of Big Five personality traits, and Fear of COVID‐19 Scale. Results The participants with anxiety had significantly higher scores for neuroticism and for the Fear of COVID‐19 Scale. The participants with depression had significantly lower scores for extraversion and higher scores for the Fear of COVID‐19 Scale. No individual background factors were significantly associated with HADS depression or anxiety scores. Conclusion Among family members of staff of a COVID‐19 frontline hospital, lower extraversion, higher neuroticism, and fear of COVID‐19 were associated with anxiety and depression. This questionnaire survey was conducted before wide‐spread rollout of COVID‐19 vaccination, so the findings of this study are expected to be applicable to other future novel infectious outbreaks.